2018
DOI: 10.1007/s11418-018-1240-8
|View full text |Cite
|
Sign up to set email alerts
|

Two new xanthones and cytotoxicity from the bark of Garcinia schomburgkiana

Abstract: Two new xanthone derivatives, named schomburgones A (1) and B (2), along with eight known compounds, including xanthones (3-8) and anthraquinones (9-10) were isolated from the bark of Garcinia schomburgkiana. Their structures were determined by spectroscopic analysis especially 1D and 2D NMR spectroscopies. All isolated compounds were evaluated for their cytotoxicity against five cancer cell lines (KB, HeLa S-3, HT-29, MCF-7 and HepG-2). Compounds 3-6 and 8 showed good cytotoxicity against all the five cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…EtOAc fractions from methanolic extracts of leaves and stems had the most active DPPH antioxidant activity and were shown to be more effective than the Trolox positive control. The ranges of antioxidant capacity obtained are within similar ranges to other species of the same family, both for DPPH and ABTS [28][29][30][31] . Likewise, F-EtOAc leaf fractions had α-glucosidase inhibitory activity, similar to other species in the Clusiaceae family 29,[32][33][34] .…”
Section: Discussionsupporting
confidence: 70%
“…EtOAc fractions from methanolic extracts of leaves and stems had the most active DPPH antioxidant activity and were shown to be more effective than the Trolox positive control. The ranges of antioxidant capacity obtained are within similar ranges to other species of the same family, both for DPPH and ABTS [28][29][30][31] . Likewise, F-EtOAc leaf fractions had α-glucosidase inhibitory activity, similar to other species in the Clusiaceae family 29,[32][33][34] .…”
Section: Discussionsupporting
confidence: 70%
“…In 2019, Kaennakam et al reported the isolation of two new xanthones, i.e., schomburgones A and B from the bark of Garcinia schomburgkiana. Unfortunately, these compounds are nonactive against HepG2, MCF-7, HT-29, HeLa S-3, and KB cancer cells, with IC 50 values of 45.05-69.22 µM [68].…”
Section: Isolation Of Xanthone Derivativesmentioning
confidence: 99%
“…Unauthorized distribution is strictly prohibited. oxyguttiferone K (9) [16], oblongifolin G (10) [17]. The chemical structures of the known compounds were confirmed by NMR spectroscopic data and comparison with previously published data.…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…Five undescribed polyprenylated benzoylphloroglucinol derivatives (1)(2)(3)(4)(5), named garschomcinols A-E, and five known analogues (6)(7)(8)(9)(10) were isolated from the branches of Garcinia schomburgkiana. Their structures were determined on the basis of 1D and 2D NMR and HRESIMS analyses.…”
Section: Introductionmentioning
confidence: 99%